REVIEW OF ASHTAVIDHA PARIKSHA W.S.R. TO NADI PARIKSHA - Anand, *Tekade; Deepali, Watkar; Kavita, Daulatkar; Mukund, Dive (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda is the science of health and diseases free life. It is the knowledge that is abundantly supplied with guidelines which, if followed scrupulously and regularly, would spare the agony of diseases. Ayurveda is based on sound of principles of diagnosis. It is not requires clinical or costly investigations. Which are beyond reach of common and less privileged person.Asthavidha Pariksha (eight fold examination) in Ayurveda is one of the important examinations to find the various causes behind the diseases. In Ashtavidha Pariksha there are eight factors which are taken into consideration during the examination and tests carried out with the patients. Also, Nadi Pariskha is one the most important examination part for diagnosis the diseases of patients.Ashtavidha pariksha: Nadi (Pulse), Mootra (Urine), Malam (Fecal matter), Jihwa (Tongue), Sabdam (Voice of patients), Sparsham (Touch), Druk (Eyes & Vision), Akriti (General body build). Nadi Pariksha plays very important role in diagnosis of the disease. According to Ayurveda, the presence of disease in our system indicates an imbalance in our â€œDoshasâ€ bringing our system back into balance is the key to the cure & with the help of Nadi Pariksha & Ayurveda doctor can detect the imbalance in the body & prescribe an effective treatment. In this article an attempt has been made to focus on Ashtavidha Pariksha with special reference to Nadi Pariksha. Hence Ahstavidha Pariskha with Nadi Pariksha plays an unique role in Ayurvedic Chikitsa.